2015
DOI: 10.1111/dme.12790
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome of weight change from pre‐pregnancy to 1–5 years post‐partum among Chinese women with prior gestational diabetes

Abstract: Aims Few studies have evaluated the effect of weight change from pre-pregnancy to post partum with the risk of cardiometabolic diseases among women with a history of gestational diabetes mellitus. The aim of this study was to evaluate the association between weight change from pre-pregnancy to 1–5 years post partum with metabolic syndrome among Chinese women with prior gestational diabetes mellitus. Methods We performed a retrospective cohort study in 1263 women with gestational diabetes mellitus at 1–5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
3
10
0
3
Order By: Relevance
“…Likewise, these findings may not apply to women with GDM diagnosed early in pregnancy. However, our frequency of metabolic syndrome is high and consistent with other reports in the literature 1416 . Still, our results may not be generalizable to the full spectrum of GDM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Likewise, these findings may not apply to women with GDM diagnosed early in pregnancy. However, our frequency of metabolic syndrome is high and consistent with other reports in the literature 1416 . Still, our results may not be generalizable to the full spectrum of GDM.…”
Section: Discussionsupporting
confidence: 93%
“…A subsequent report from Denmark evaluated 481 women with a previous diagnosis of GDM at a median of 9.8 years (interquartile range 6.4 – 17.2 years) after delivery and diagnosed metabolic syndrome in 38.4% 15 . Most recently, Li and colleagues reported on 1263 Chinese women with a previous diagnosis of GDM, with 23.8% of them having a diagnosis of metabolic syndrome at 1–5 years after delivery 16 . These incidence figures (23.8 – 38.4 percent) are similar to our findings (32.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our previous work has already demonstrated that GDM women with large weight gain from pre-pregnancy to post-partum were more likely to develop the metabolic syndrome (ref. 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…All pregnant women living in the six urban districts of Tianjin have been screened for GDM at their 26–30 gestational weeks from 1999 (ref. 16 ). First, they participate in a one-hour oral glucose tolerance test (OGTT) with 50-g glucose load in their community health centers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation